PATTERNS AND CAUSES OF MARITAL CONFLICT AMONG STAFF OF SELECTED UNIVERSITIES IN SOUTHWEST NIGERIA - Olugbenga, Agboola Johnson (Advances in Social Sciences Research Journal, 2018)
This study investigated the patterns and causes of marital conflict among staff of universities in southwest Nigeria. The study adopted descriptive survey design. The study sample was 1330 married staff members proportionately selected from nine universities using multi-stage sampling technique. Prevalence of Patterns of Marital Interaction Questionnaire (PPMIQ) and Causes of Marital Conflict Questionnaire (CMCQ) were used to collect data for the study. The results showed that 67.1% of the staff indicated that they experienced demand-withdraw pattern, while 26.8% experienced constructive pattern. Only 6.1% experienced destructive pattern. The results also showed that poor handling of family finances was considered as the most prominent with the highest RSI value of 0.806 followed by communication gap and time devoted to children with very high values of RSI of 0.804 and 0.7933 respectively. The least popular cause of marital conflict was difference in income level with the least RSI value of 0.681.